(untitled) (Journal of the Bangladesh Agricultural University, 2011)
The research was undertaken to know the effects of different level of sugar and mixed culture on qualitative characteristics of dahi. Milk samples were collected and boiled to reduce the 20% of their volume and divided into four portions after boiling. Sugar was added at 8, 10, 12 and 14% of of milk and boiled again for a while. After boiling milk samples were cooled down to 37°C and 1, 2, 3 and 4% mixed culture was added in each of the four level sugar added milk. The combination of 4 × 4 = 16 samples were prepared and were incubated at 37°C in an incubator until coagulation. From the organoleptic evaluation it was found that dahi samples prepared by adding 10 and 12% sugar level obtained more score then that of the 8 and 14% sugar added dahi samples. Culture level and sugar level both had influence on coagulation time. Coagulation time was less when low sugar and high level of culture was used, on the other hand coagulation time was more when high level sugar and low level culture was used. Chemical analysis showed that total solids and solids-not-fat, protein, carbohydrates content of dahi samples were significantly increased due to the increased level of sugar and culture. But on other parameters effects of sugar and culture were not appreciable. It was concluded that sugar level and culture level both can changes the quality of dahi samples. A combination of 10% sugar with 2% culture and 12% sugar with 3% culture was found appropriate for dahi making. Keywords: Misti Dahi; Starter Culture; Manufacture DOI: 10.3329/jbau.v8i2.7933 J. Bangladesh Agril. Univ. 8(2): 245-252, 2010